A fuzzy analysis framework for waste incineration power plant comprehensive benefit evaluation from refuse classification perspective. (10th June 2020) - Wu, Yunna; Tao, Yao; Deng, Zhongqing; Zhou, Jianli; Xu, Chuanbo; Zhang, Buyuan
Abstract: The waste-to-energy project has been concerned a lot due to its environmental friendliness. With the implementation of refuse classification, the utilization rate of resources has been improved and the comprehensive benefit of incineration power plant has been impacted as well. Thus, to assess the incineration power plant performance from refuse classification perspective, the article constructs a complete decision framework. Firstly, 13 sub-criteria are identified into 3 categories and the hesitant fuzzy linguistic term sets (HFLTS) is employed to ensure the completeness of evaluation information. Secondly, the analytic hierarchy process (AHP) method and entropy method are combined to obtain the indexes weights, avoiding the subjectivity in weight judgment. Thirdly, based on principle of fuzzy relation synthesis, fuzzy synthetic evaluation (FSE) method is used to calculate the final result. A case study is carried out to validate the applicability of the proposed framework. In addition, the article puts forward suggestions in economics, environment and society to improve the overall benefit of incineration power plant. From a new perspective, this paper provides a theoretical reference for the future development of incineration power plants and expands literature in benefit evaluation. Highlights: A decision framework for incineration power plant comprehensive benefit evaluation from refuse classification perspective. A novel index system for incineration power plant comprehensive benefit evaluation is established. HFLTS, TFN, combined weight method and FSE method are employed in the decision-making process. Effective improvements are proposed to raise the comprehensive benefit.